Selecting KB Villages Using the VIKOR Method: A Case Study DPPKB Labuhanbatu - Nasution, Anggi Refachriati; Samsudin, Samsudin (Universitas Bina Darma, 2024)
Technological advancements have taken place in various fields. Health, education, business, and decision-making are no exception. The KB program was created in order to echo the KB program as an effort to strengthen the KKBPK program and span the birth rate. Therefore, a decision support system using the vikor method was created. The research process was carried out at DPPKB Labuhanbatu. Data collection was carried out by conducting direct interviews to the object of research, namely DPPKB Labuhanbatu. The criteria in this study are the number of pre-prosperous households, the number of family planning participants, regional criteria, the existence of family data and maps, the number of elementary school age population, the number of MKJP, the number of unmet needs, family participation in the family resilience development program, family participation in the family economic improvement empowerment program, youth participation in planning generation activities. This research uses the R&D research method and uses the waterfall method in its system development method. The final result of this study found that the selected KB village was Perbaungan village with an index of 0, second place Bandar Kumbul village with index 0.0588 where the alternative with the minimum Q value was the highest rank.